2012
DOI: 10.1002/mnfr.201100500
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carotene and lycopene affect endothelial response to TNF‐α reducing nitro‐oxidative stress and interaction with monocytes

Abstract: Our observations provide background for a novel mechanism for carotenoids' anti-inflammatory activity in the vasculature and may contribute to a better understanding of the protective effects of carotenoid-rich diets against CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 42 publications
3
70
0
1
Order By: Relevance
“…Di Tomo et al (2012) reported that low concentration of b-carotene (2.5 lM) decreased ROS generation in TNF-a-treated human umbilical vein endothelial cells. Gloria et al (2014) showed that b-carotene and lycopene (0.5-10 lM) induce cell cycle arrest, growth inhibition, and apoptosis in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Tomo et al (2012) reported that low concentration of b-carotene (2.5 lM) decreased ROS generation in TNF-a-treated human umbilical vein endothelial cells. Gloria et al (2014) showed that b-carotene and lycopene (0.5-10 lM) induce cell cycle arrest, growth inhibition, and apoptosis in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As possible mechanisms for anticancer effect of b-carotene, pro-oxidant activity (Palozza et al 2002;Guruvayoorappan and Kuttan 2007), anti-oxidant action (Di Tomo et al 2012;Mishra et al 2013), and cell cycle regulation (Lim et al 2014;Gloria et al 2014) have been demonstrated. Di Tomo et al (2012) reported that low concentration of b-carotene (2.5 lM) decreased ROS generation in TNF-a-treated human umbilical vein endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…These functions decreased interactions of endothelial cells with monocytes [43]. Another report demonstrated that β-carotene and lycopene treatment reduced TNF-α-induced oxidative stress and inflammatory responses to affect interactions between monocytes and human endothelial cells [43]. Furthermore, lycopene reduces C-reactive protein levels in CVD [49].…”
Section: Preventive Effects Of Carotenoids On Cardiovascular Disease mentioning
confidence: 99%
“…Furthermore, β-carotene and lycopene reduced TNF-α-enhanced inflammatory responses by reducing nitro-oxidative stress. These functions decreased interactions of endothelial cells with monocytes [43]. Another report demonstrated that β-carotene and lycopene treatment reduced TNF-α-induced oxidative stress and inflammatory responses to affect interactions between monocytes and human endothelial cells [43].…”
Section: Preventive Effects Of Carotenoids On Cardiovascular Disease mentioning
confidence: 99%
See 1 more Smart Citation